Lactate concentration after final team judo matches - Trivic, T.; Drid, P.; Todorov, I. (4th European Science of Judo Symposium. Budapest, April 25th 2013, 2013)
Blood lactate has been usually examined during the training or in laboratory conditions. Purpose of this study was to investigate lactate concentration after warming up before competition, as well as after final matches on Serbian team championship for male judokas. Research was conducted on two groups of five judokas divided in five weight category. Blood samples were collected from the ear lobe in order to measure lactate concentration before and after two final matches. Based on the obtained results statistical significance differences were noted between first and second final matches in lactate concentration in booth groups of male judokas. After second match booth group of judokas had higher value of lactate concentration, which indicates a need for improvement of anaerobic capacity. High value of lactate concentration after second match increase muscle acidity, which causes an increase in fatigue. It can be concluded that Serbian male judokas need to improve anaerobic capacity in order to sustain more matches during the competition. This research points out the need to design strategies in training program that clears blood lactate after high intensity matches which enables a faster recovery during the competition.